ChemInform Abstract: Silica Monoliths with Hierarchical Porosity Obtained from Porous Glasses. Issue 28 (21st June 2013) - Inayat, Alexandra; Reinhardt, Bjoern; Uhlig, Hans; Einicke, Wolf‐Dietrich; Enke, Dirk
Abstract Review: synthetic strategies for the introduction of hierarchy into "classical" porous glass monoliths; 42 refs.